Sclerostin Suppression Facilitates Uveal Melanoma Progression Through Activating Wnt/β-Catenin Signaling Via Binding to Membrane Receptors LRP5/LRP6 - Wang, Hanqing; Zhao, Sidi; Liu, Yang; Sun, Fengyuan; Huang, Xiaoming; Wu, Tong (Frontiers in Oncology, 2022)
Objective Uveal melanoma (UM) is the most frequent primary eye cancer in adults with a 50% mortality rate. Characterizing the fundamental signaling pathways that drive UM is of importance for the development of targeted therapy. This study aims to probe the impact of sclerostin (SOST) on malignant progression of UM and regulation of Wnt/β-catenin signaling. Methods Epithelial-type (n=20) and spindle-type (n=16) UM tissues were collected for immunohistochemical staining of SOST, Wnt-1, and β-catenin expressions. SOST was silenced in three UM cell lines (primary spindle-type OCM-1 cells, metastatic epithelial Mum-2B cells, and metastatic spindle-type Mum-2C cells) through transfecting specific siRNA. RT-qPCR and Western blot were presented for examining the levels of SOST, and markers in Wnt/β-catenin signaling. Flow cytometry, MTT, EdU, transwell, and tube formation assays were conducted, respectively. By implanting BALB/c nude murine models in situ, the function of SOST on tumor growth was investigated, followed by immunofluorescence double staining of SOST and LRP5/6. Results Low SOST expression as well as high Wnt-1 and β-catenin expressions were found in epithelial-type (high malignancy) than spindle-type (low malignancy) UM tissues. Silencing SOST activated the markers in Wnt/β-catenin signaling as well as accelerated cell cycle progression, migration, invasion, angiogenesis, and reduced apoptosis in UM cells. In situ tumor formation in murine eyes showed that SOST knockdown promoted tumor growth. Moreover, SOST interacted with LRP5/LRP6. Conclusion SOST silencing may facilitate the malignant progression of UM cells through activating Wnt/β-catenin signaling. Mechanistically, SOST may exert this function by interacting with LRP5/LRP6 membrane receptors.